Biodiesel production optimization using monolithic catalyst in a fixed-bed membrane reactor. (1st November 2015) - Xu, Wei; Gao, Lijing; Xiao, Guomin
Highlights: Ca–Mg–Al hydrotalcite was in-situ synthesized on honeycomb ceramic. A new monolithic catalyst was used for biodiesel production in membrane reactor. Central composite design was employed to analyze and optimize the process. Abstract: In this study, Ca–Mg–Al hydrotalcite was deposited on the inert honeycomb ceramic surface as a second carrier and KF was loaded on the support as an active component. The KF/Ca–Mg–Al hydrotalcite/honeycomb ceramic monolithic catalyst was packed in the membrane reactor for biodiesel production from the transesterification between soybean oil and methanol. The central composite design (CCD) of response surface methodology (RSM) was employed to investigate the effects of reaction temperature, catalyst amount and circulation velocity on the production of biodiesel. A quadratic model was developed to navigate the design space. The optimum condition for the highest biodiesel yield was obtained by the assistance of the model. The catalyst showed a reasonable efficiency and reusability for coupling the monolithic catalyzed transesterification and membrane separation in the membrane reactor.